2019
DOI: 10.14254/2071-8330.2019/12-3/15
|View full text |Cite
|
Sign up to set email alerts
|

Debt policy of companies in Czech Republic

Abstract: The attitude of companies towards the use of debt depends on many factors that can be generally called corporate debt policy. This paper deals with the debt policy of companies in Czech Republic, focusing on the factors affecting the appropriate amount of debt and their debt policy in general. The aim of this contribution is to reveal the dominant factors affecting companies in their debt policy decisions and to analyse the possible impact of the selected classifying factors on the firms' responses. The findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…Strýčková (2017) reported that Czech companies follow a pecking order in their financing mix and exhibit both the differences and similarities with their European and American counterparts. Similar results were reported by Strýčková (2019), providing yet more support for the pecking-order theory in Czech companies, where insufficiency of the internal finances and the earnings volatility were found to be the most significant factor for designing a firms' debt policy. Chen (2004) demonstrated that due to the differences in the institutional structure like the ownership concentration, financial constraints and legal structure, the firms in China follow a new pecking-order theory, i.e., retained earnings, then equity, and debt only as a last resort.…”
Section: Literature Reviewsupporting
confidence: 85%
“…Strýčková (2017) reported that Czech companies follow a pecking order in their financing mix and exhibit both the differences and similarities with their European and American counterparts. Similar results were reported by Strýčková (2019), providing yet more support for the pecking-order theory in Czech companies, where insufficiency of the internal finances and the earnings volatility were found to be the most significant factor for designing a firms' debt policy. Chen (2004) demonstrated that due to the differences in the institutional structure like the ownership concentration, financial constraints and legal structure, the firms in China follow a new pecking-order theory, i.e., retained earnings, then equity, and debt only as a last resort.…”
Section: Literature Reviewsupporting
confidence: 85%
“…Perusahaan dapat menjalankan debt policy apabila mengalami kekurangan dana atau membutuhkan tambahan dana. Pendanaan dari luar dengan menggunakan utang dapat memberikan sejumlah keuntungan bagi perusahaan, tetapi apabila digunakan berlebihan dan tidak direncanakan dengan baik dapat menimbulkan masalah yang serius dan timbulnya risiko (Strýčková 2019). Manajer di setiap perusahaan harus bisa mempertimbangkan risiko atas penggunaan utang dan memastikan proporsi penggunaan utang sudah sesuai.…”
Section: Debt Policy Dan Nilai Perusahaanunclassified
“…Debt financing enables a business to, among other things, consider and take advantage of investment opportunities that can help increase its value. In contrast, the excessive use of debt financing can cause a number of problems for a business [15]. The use of external capital for financing a business comes with the risk of bankruptcy [16].…”
Section: Literature Reviewmentioning
confidence: 99%